2018
DOI: 10.1038/s41598-018-23640-8
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Serum Amino Acid Profile for Induction of Hepatic Steatosis under Protein Malnutrition

Abstract: We previously reported that a low-protein diet caused animals to develop fatty liver containing a high level of triglycerides (TG), similar to the human nutritional disorder “kwashiorkor”. To investigate the underlying mechanisms, we cultured hepatocytes in amino acid-sufficient or deficient medium. Surprisingly, the intracellular TG level was increased by amino acid deficiency without addition of any lipids or hormones, accompanied by enhanced lipid synthesis, indicating that hepatocytes themselves monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 35 publications
0
49
0
2
Order By: Relevance
“…The values are the means ± standard errors. Asterisks indicate significant differences assessed by one-way ANOVA with Bonferroni and Tukey-Kramer post-hoc tests (*p < 0.05) methionine and histidine, were significantly increased by a low Arg diet [10]. Therefore we do not consider arginine alone a signal molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values are the means ± standard errors. Asterisks indicate significant differences assessed by one-way ANOVA with Bonferroni and Tukey-Kramer post-hoc tests (*p < 0.05) methionine and histidine, were significantly increased by a low Arg diet [10]. Therefore we do not consider arginine alone a signal molecule.…”
Section: Discussionmentioning
confidence: 99%
“…We previously investigated the impacts of various amino acids on fat accumulation in the liver using amino acid-deficient diets, and the results showed that the liver triglyceride (TG) content could be increased only by a deficiency of arginine out of the 20 major amino acids tested [10]. Therefore, we hypothesized that lipid accumulation in the liver induced by dietary amino acid deficiency could be attributed to increased insulin sensitivity, which may be caused specifically by dietary arginine deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of this pathway is known to upregulate FFA synthesis [9,[29][30][31], and, indeed, increased de novo lipogenesis was observed in 5PAA dietfed rats. In contrast, we recently reported that when hepatocytes were cultured in an amino acid-su cient or -de cient medium, the intracellular TG level was increased by amino acid de ciency without the addition of any lipids or hormones, and was accompanied by enhanced lipid synthesis [10]. These results indicate that hepatocytes themselves monitor extracellular amino acid concentrations to induce lipid accumulation in a cell-autonomous manner.…”
Section: Discussionmentioning
confidence: 76%
“…The activation of this pathway is known to upregulate FFA synthesis [9,[29][30][31], and, indeed, increased de novo lipogenesis was observed in 5PAA diet-fed rats. In contrast, we recently reported that when hepatocytes were cultured in an amino acidsu cient or -de cient medium, the intracellular TG level was increased by amino acid de ciency without the addition of any lipids or hormones, and was accompanied by enhanced lipid synthesis [10]. These results indicate that hepatocytes themselves monitor extracellular amino acid concentrations to induce lipid accumulation in a cell-autonomous manner.…”
Section: Discussionmentioning
confidence: 76%
“…We previously investigated the impacts of various amino acids on fat accumulation in the liver using amino acid-de cient diets, and the results showed that the liver triglyceride (TG) content could be increased only by a de ciency of arginine out of the 20 major amino acids tested [10]. Therefore, we hypothesized that lipid accumulation in the liver induced by dietary amino acid de ciency could be attributed to increased insulin sensitivity, which may be caused speci cally by dietary arginine de ciency.…”
Section: Introductionmentioning
confidence: 99%